Farmers' Perceptions of the Impact of Climate Change and Their Adaptation Strategies in Rice Farming in Sibulue Subdistrict, Bone Regency, South Sulawesi Province - Ekawati, Dian; Saediman; Yusria (International journal of technology and education research, 2025)
This study aims to: (1) determine farmers' perceptions of climate change, (2) determine farmers' perceptions of the impact of climate change on rice paddy production, and (3) their adaptation strategies in rice paddy farming in Sibulue District, Bone Regency, South Sulawesi Province. The sample determination used a census. So the number of selected farmer samples was 38 farmers. The analysis used was descriptive analysis by combining scoring, in this case, the question items will be given answers according to a 5-level Likert scale where the Likert scale has 2 forms of statements, namely positive statements and negative statements, and descriptive statistical analysis by combining scoring and percentages of respondents' answers. The results of the study showed that farmers' perceptions of climate change in Sibulue District, Bone Regency included the frequency and intensity of rainfall becoming uncertain in the high category (3.74), and more frequent flooding in the category (3.51). Farmers' perceptions regarding the impact of climate change on rice farming production in Sibulue District, Bone Regency include crop damage due to strong winds in the high category (3.78), and reduced access to food in the category (3.51). Rice farmers' adaptation strategies in facing climate change in Sibulue District, Bone Regency include using superior varieties or seeds (95%), using climate-smart technology (95%), changing cropping patterns (92%), cultivating other crops on dry land (89%), using pesticides (new types, increasing or decreasing the dosage) (89%), adjusting planting times (82%), and changing irrigation techniques (82%).